1994
DOI: 10.1073/pnas.91.14.6712
|View full text |Cite
|
Sign up to set email alerts
|

The Fanconi anemia polypeptide FACC is localized to the cytoplasm.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(52 citation statements)
references
References 22 publications
2
49
0
1
Order By: Relevance
“…Yamashita et al (5) have also observed a similar association of FAC with cellular proteins in immunocomplexes. Although these studies suggest that FAC is capable of forming a multimeric complex in vitro, the biological significance of these associations is unclear.…”
Section: Introductionmentioning
confidence: 68%
“…Yamashita et al (5) have also observed a similar association of FAC with cellular proteins in immunocomplexes. Although these studies suggest that FAC is capable of forming a multimeric complex in vitro, the biological significance of these associations is unclear.…”
Section: Introductionmentioning
confidence: 68%
“…13,14 The human FANCG has a putative leucine zipper motif, but it is not conserved in the mammalian homologs. 15 FANCC has a predominantly cytoplasmic localization, 16,17 with a smaller fraction present in the nucleus. 18 The FANCA, FANCF, and FANCG proteins are found predominantly in the nucleus, with some cytoplasmic localization.…”
Section: Introductionmentioning
confidence: 99%
“…The FANCC gene, cloned by functional complementation of FA-C cells, encodes a protein of 558 amino acids with a molecular mass of 63 kd. 8 The cellular localization of FANCC protein is mostly cytoplasmic, 14,15 but a fraction of this protein does translocate into nuclei. [16][17][18][19] The FANCA gene encodes a protein of 1455 amino acids with a molecular mass of approximately 163 kd.…”
Section: Introductionmentioning
confidence: 99%